A randomized controlled trial to assess the effect of a medication plan containing drug administration recommendations on patients’ drug knowledge after 2 months - Send, Alexander Francesco Josef; Peters-Klimm, Frank; Bruckner, Thomas; Haefeli, Walter E.; Seidling, Hanna (Journal of clinical pharmacy and therapeutics, 2017)
What is known and objective Patients’ drug administration errors are often promoted by poor drug knowledge resulting from inadequate oral or written information. It has previously been shown that a medication plan enhanced with graphical and textual information on drug handling (enhanced medication plan) proved to immediately increase patients’ drug knowledge. This study aimed to evaluate the effect of the enhanced medication plan on drug knowledge in outpatients after 2 months (intervention group) compared to patients with a simple medication plan with standard information (control group). Methods We recruited patients using ≥5 drugs in four family practices in Germany. After inclusion, patients’ knowledge on handling of their drugs was assessed using three questions from a standardized catalog. Thereafter, patients were randomized to the intervention or control group. After 2 months, drug knowledge was reassessed with three different questions from the same standardized catalog. Results and discussion Of 120 enrolled patients, 75% of participants in the control group (42/60 patients) and 78% of participants in the intervention group (46/60; P = 0·71) completed the study. Baseline drug knowledge was similar in both groups (43·7% vs. 40·6% correct answers). After 2 months, patients’ drug knowledge showed an absolute increase of 23·2% in the intervention group (P < 0·01) and was unchanged in the control group (46·0%; P = 0·70). What is new and conclusion The enhanced medication plan outperformed the effect of a simple medication plan and persistently increased the fraction of correct answers of polypharmacy patients. This demonstrates that the enhanced medication plan may be a useful tool in promoting drug knowledge.